From transgression to decriminalization: A path to promote legitimacy, inclusion, and democracy in Latin America - Moriconi, M. (Middle Atlantic Review of Latin American Studies, 2024)
Despite the extensive literature developed and published in recent decades on the causes of crime in Latin America and its solutions, data show that crime is consolidating and growing in the region. This essay warns that one of the crucial errors in much of that literature is the confusion between means and ends. Crime, like democracy, is a means to an end, and rather than good or bad, means are either effective or ineffective. Researchers have shown that in many Latin American countries, legality, as a categorical imperative and model of life, has lost legitimacy, truthfulness, and effectiveness, and transgression has become an admired value. Growth in crime is closely related to this environment. Instead of debating the quality of democracies, this essay explains the importance of discussing the concept of worthwhile lives and reviewing the scope of legality in Latin America. We suggest that the premise of governing to include is crucially related to the need to redefine the scope of what is legal. And in that debate, the decriminalization of drugs is a central chapter.